Analisis Pemberitaan Potensi Angin di Media Online untuk Merealisasikan Pembangkit Listrik Tenaga Bayu di Kabupaten Wonogiri - Nadhiroh Nadhiroh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2020)
Wonogiri Regency has great natural resource potential. Among them are water and wind in the Gajah Mungkur Reservoir (WGM) and the surrounding area. This study analyzes the importance of reporting on wind potential in Wonogiri Regency. Many news about the potential of water in the Gajah Mungkur Reservoir have been discussed. Meanwhile, the potential for wind has not been reported much. So far, based on the author's observations and several samples of writing in online media, the news about the potential for wind or wind has been mostly for entertaining activities such as kite festivals, paragliding and hang gliding. The function of online media is like the function of the press, which is to provide information, educate, entertain and act as social control. This study seeks to analyze the importance of potential wind news in Wonogiri Regency in Online Media. In some samples of news in online media, there is not much about the potential for wind in Wonogiri District. The potential for wind in Wonogiri if it is continuously raised and reported can get attention and support the existence of a wind power plant. Through this research, the researcher hopes that the news about the potential of the wind will be maximized to raise these natural resources for something that is more beneficial to society. For example, for wind power plants (PLTB).